2015
DOI: 10.1177/1934578x1501000723
|View full text |Cite
|
Sign up to set email alerts
|

Antileishmanial Activity of Compounds Isolated from Sassafras albidum

Abstract: Leishmaniasis is a neglected tropical disease caused by Leishmania parasitic protozoa, which currently lacks efficient treatment. Natural products have shown promise as a potential source for antiprotozoal drugs. This work focuses on the antileishmanial potential of Sassafras albidum (Lauraceae) bark extract. The crude bark extract of S. albidum showed excellent antileishmanial activity with an IC50 value less than 12.5 μg/mL against promastigotes of L. amazonensis. The chloroform stem bark extract of S. albid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Plantderived β-sitosterol has also been studied against different forms of leishmaniasis; for example, phytosterols (stigmasterol + β-sitosterol) isolated from Musa paradisiaca fruit peel have been tested for antileishmanial properties in vitro by studying growth inhibition of L. infantum chagasi promastigotes and amastigotes 19 . Similarly, β-sitosterol isolated with other components from Sassafras albidum stem bark was studied against Leishmania amazonensis, where the β-sitosterol was found to be least effective against the promastigotes, which was evident from its highest IC 50 value in comparison to that of the other isolated products 17 . Furthermore, although the leishmanicidal effect of β-sitosterol from Ifloga spicata showed apoptosis-type killing of L. tropica promastigotes, the detailed mechanism of apoptosis is unclear 18 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plantderived β-sitosterol has also been studied against different forms of leishmaniasis; for example, phytosterols (stigmasterol + β-sitosterol) isolated from Musa paradisiaca fruit peel have been tested for antileishmanial properties in vitro by studying growth inhibition of L. infantum chagasi promastigotes and amastigotes 19 . Similarly, β-sitosterol isolated with other components from Sassafras albidum stem bark was studied against Leishmania amazonensis, where the β-sitosterol was found to be least effective against the promastigotes, which was evident from its highest IC 50 value in comparison to that of the other isolated products 17 . Furthermore, although the leishmanicidal effect of β-sitosterol from Ifloga spicata showed apoptosis-type killing of L. tropica promastigotes, the detailed mechanism of apoptosis is unclear 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, despite the many studies on the effect of plant-derived β-sitosterol on various forms of leishmaniasis, the mechanisms by which the compound kills the parasites remain unclear. On the basis of previous reports, it could be suggested that although the effect of different plant-derived β-sitosterols has been examined on various Leishmania spp., the effectiveness varies among different Leishmania species and strains [16][17][18][19]35 . The discrepancy in the efficacy of drugs depends on the phenotypic variability of different species or strains, clinical appearances and geographical origin 36,37. Certain antileishmanial drugs have also been reported to exhibit species-and strain-specific efficiency 37-40. Additionally, various plant-derived secondary metabolites have been shown to exhibit target-specific activity against parasites 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhizome: alkaloids (sanguinarine and chelerythrine-antimycobacterial) [452] Rhizome: alkaloids (sanguinarine, chelerythrine, protopineanti-Helicobacter pylori) [453] Rhizome: alkaloids [sanguinarine (2.81-3.96%), chelerythrine (1.38-2.08%)] [454] Rhizome: alkaloids (sanguinarine, chelerythrine, sanguilutine, chelilutine, sanguirubine, chelirubine, protopine, and allocryptopine) Root EO: safrole (85%), camphor (3.25%), and methyleugenol (1.10%) [457] Bark EO: α-pinene (37.9-61.5%), camphene (2.9-5.1%), β-pinene (10.0-13.0%), 1,8-cineole (7.3-10.0%), camphor (1.7-4.6%), and α-terpineol (4.2-11.6%) [458] Bark: sesamin, spinescin, β-sitosterol, hexatriacontanal, and 1-triacontanol; sesamin and spinescin showed antileishmanial activity [459] Saururus cernuus L. Saururaceae Lizard s tail mashed roots poultice for wounds root [15] Aerial parts: lignans (austrobailignan-5, veraguensin, guaiacin, saucernetin) [460] Plant: lignans (manassantin A, manassantin B, saucerneol) [461] Aerial parts: indole alkaloids (sauristolactam, cepharanone B) [462] Aerial parts: lignans (saururin, saururenin, saururinone, austrobailignan 6, calopiptin, galbacin, zuonin A) [463] Aerial parts: lignans (sauriol A, sauriol B) [464] Aerial parts: lignans (licarin A, saucernetin, dihydroguaiaretic acid, sauriol A, sauriol B, saucerneol, and saucerneol methyl ether) [465] Aerial parts: diterpenoid 12,13-dehydrogeranylgeraniol [466] Aerial parts: lignans (manassantin B, 4-O-demethylmanassantin B) [467] Stems and leaves: lignans (manassantin A, manassantin B, manassantin B 1 , 4-O-methylsaucerneol, verrucosin, austrobailignan- Aerial parts EO: δ-cadinene (27%), calamenene (15.2%), β-elemene (9.2%), α-cubenene (4.2%), α-humulene (4.2%), and α-bergamotene (2.8%) [470] Aerial parts: neo-clerodane diterpenoids (scutelaterin A, scutelaterin B, scutelaterin C, ajugapitin, and scutecyprol A) [471] Herb: flavonoids baicalin and baicalein (aglycone) [472] Aerial parts: indole alkaloids (melatonin, serotonin); flavonoids (baicalin, baicalein, wogonin, scutellarin) [473] Herb: flavonoids (viscidulin III, chrysin, baicalein, oroxylin A, wogonin); phenolics (trans-verbascoside, trans-martynoside) [474] Aerial parts: coumarins (scuteflorin A, scuteflorin B, decursin) [475] Stem Senecio aureus L. Asteraceae Golden ragwort infusion of plant taken to prevent pregnancy/induce abortions plant [15] Eremophilane sesquiterpenoids (trans-9-oxofuranoeremophilane...…”
Section: Asteraceaementioning
confidence: 99%
“…The in vitro antileishmanial analysis of MeOH extract and its SPE were estimated by the method described by (Pulivarthi et al 2015…”
Section: In Vitro Antileishmanial Analysismentioning
confidence: 99%